Answer: 19.625
Step-by-step explanation: if u need the explanation add me
You need to subtract everything to the left side and set it equal to zero. Combine like terms.
Then, the coefficient of x^2 is a, the coefficient of x is b, and the constant term is c.
4x^2 - 5 = 3x + 4
4x^2 - 3x - 5 - 4 = 0
4x^2 - 3x - 9 = 0
a = 4; b = -3; c = -9
![x = \dfrac{-b \pm \sqrt{b^2 - 4ac}}{2a}](https://tex.z-dn.net/?f=%20x%20%3D%20%5Cdfrac%7B-b%20%5Cpm%20%5Csqrt%7Bb%5E2%20-%204ac%7D%7D%7B2a%7D%20)
![x = \dfrac{-(-3) \pm \sqrt{(-3)^2 - 4(4)(-9)}}{2(4)}](https://tex.z-dn.net/?f=%20x%20%3D%20%5Cdfrac%7B-%28-3%29%20%5Cpm%20%5Csqrt%7B%28-3%29%5E2%20-%204%284%29%28-9%29%7D%7D%7B2%284%29%7D%20)
Answer:
10 + x
Step-by-step explanation:
Sum means add
Hope this helps you :)
pls give me brainlest ;)
Answer:
y= -2x-3
Step-by-step explanation:
this is because the y intercept is at negative 3 and the rise over run is down 1 over 2